KLASIFIKASI KATA WARNA PADA MASYARAKAT MELAYU SAMBAS - Syafika, Syafika; Heryana, Nanang; Jupitasari, Mellisa (Universitas Tanjungpura, 2023)
Color is the conveyance of ideas and information from its users. Likewise, the life of the Malays in Sambas Regency cannot be separated from color. This canbe seen from their penchant for striking color combinations and the formation of unique color naming. The method used is descriptive in the form of qualitative research. Which aims to describe (1) the lingual unit of color markers and the cultural meaning of the concept of using color. The approach used is ethnolinguistics. The data source is in the form of lingual units from the speech of the Sambas Malay community. Collecting data using note-taking techniques and documentary studies, researchers as a data collection tool. The results showed thatthe Sambas Malay community recognized 9 color names, namely putteh 'white', ittam' black', red 'red', ijjau 'green', yellow 'yellow', brown 'chocolate', gray 'gray'and 2 non- basic colors are blue 'blue' and manganese 'purple'. 75 derivative colors were found with adjective, noun, and verb attributes from the nine colors. The most dominating attribute is the plant noun. Second, the cultural meaning of the concept of using color in the Sambas Malay community is divided into verbal and non-verbal domains. There are 4 colors used in the verbal domain, namely putteh 'white', ittam 'black', red 'red', and ijjau 'green'. Furthermore, there are 4 colors used in the nonverbal domain, including putteh 'white', ijjau 'green', yellow'yellow', and red 'red'.